Finite Element Model Updating Using FRF Measurements. (2005) - Asma, Farid; Bouazzouni, Amar
Abstract : This study presents a new updating method based on measured frequency response functions. The objective function of the minimization procedure is formed by the difference between the measured and the analytical frequency responses. The updating parameters are the correction coefficients related to each the elementary mass and stiffness matrices. While making use of a number of incomplete measurements for some frequencies, one builds a non-linear system of equations. The linearisation of the numerical system leads to an iterative procedure. An intrinsic frequency parametrization is proposed in order to accelerate the convergence of the iterative system. The obtained results are comparable with those of the known least squares methods.